Anthropometry of 12-Year-Old Football Athletes in Central Java - Mohamad Annas; Soegiyanto KS; Taufik Hidayat; Mugiyo Hartono; Adi S (International Conference on Science, Education, and Technology, 2022)
Abstract. One of the essential factors in talent scouting is anthropometry. This study aims to determine the anthropometry of SSB KU 12 students. This research method is quantitative and non-experimental. The number of samples in this study was 201 football athletes in Central Java. Sample selection total sampling. This study observed several items: height, weight, head circumference, arm circumference, abdominal circumference, thigh circumference, chest circumference, arm length, and leg length. Anthropometric factors are essential in fostering football achievement. This study still has limitations in determining the criteria for athletes. The results of this study are used as a reference in making decisions. Hopefully, there will be further research on fat mass and football athletes' technical, physical, and psychological aspects.